PELATIHAN PENULISAN DAN PEMBUATAN BAHAN AJAR RESPONDEN GENDER BAGI GURU SEKOLAH MENENGAH PERTAMA - Pairulsyah, Pairulsyah; Susetyo, Susetyo; Syani, Abdul; Suwarno, Suwarno (Prosiding Pengabdian FISIP Unila, 2012)
This training aims to increase participants understanding of the concept and scope of gender,  gender  policy  in education,  gender  issues  in schools,  identify the gender gap  in schools,  identifying  and  formulating  gender  responsive  teaching materials.  The methods used  are  lectures, discussion, group work,  discussions, and presentations.  Training results  indicate  that,  first, there was a  significant improvement of the understanding of gender mainstreaming in education. Second, an increase in  the skills  on how to identify  gender  issues,  redefined  gender responsive education policy, and create regional action programs or activities on gender-responsive education. Third, there is increased awareness and commitment of  the participants  on the importance of  implementing  gender mainstreaming gender-responsive education of each school . Keywords: Teaching materials, Gender